PENDIDIKAN REPRODUKSI REMAJA SEBAGAI UPAYA MEMINIMALISIR PROBLEM SEKSUAL - Imas Jihan Syah (Universitas Islam Lamongan, 2017)
one of the serious problems facing the adolescents is the rise of promiscuity potentially leading to free sex. This problem becomes more severe when the existence of schools could no longer contribute more. Thus, one of the efforts to minimize the promiscuity is by optimizing counseling programs that specifically deal with adolescent reproductive health. In this paper, the writer will describe the relevance as well as the urgency of adolescent reproductive education taking counseling media to reduce the problem of adolescent sexuality. On this stand, educational practitioners are expectedly able to define the educational gap that is now more focused on the development of science by overriding the problems experienced by students who are also teenagers.Keywords: Reproductive Education, Sexual Problems